1969
DOI: 10.1136/sti.45.4.299
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic properties of the protein component of Treponema pallidum.

Abstract: In a previous paper (Metzger and Podwiinska, 1967) evidence was presented that the development of agglutinability which occurs in ageing suspensions of T. pallidum (Hardy andNell, 1955, 1957; Metzger and Podwinska, 1965) (2) Each batch of treponeme suspensions under (i), (ii), and (iii), prepared anew for every immunization week, was tested for virulence by injecting 01 ml. of the suspension containing 29 million organisms at each of four sites on the shaven back of a rabbit, and 0 5 ml., 299

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

1969
1969
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…The results previously reported (Metzger, Michalska, Podwin'ska, and Smog6r, 1969) have thus been corroborated and extended.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results previously reported (Metzger, Michalska, Podwin'ska, and Smog6r, 1969) have thus been corroborated and extended.…”
Section: Discussionsupporting
confidence: 79%
“…
The results reported in a previous paper (Metzger, Michalska, Podwiriska, and Smog6r, 1969) have clearly shown that the immunogenic properties of Treponema pallidum are related to their protein component. A high degree of immunity to challenge inoculation by virulent treponemes was obtained in rabbits that had been injected with killed treponemes with the protein antigen preserved, as judged by their high agglutinability in a serum that contained antibody to this component only.
…”
mentioning
confidence: 68%
“…The results, therefore, of three groups of investigators are of interest, viz. Tani, Inoue, and Asano (1951), Miller (1967, 1973, Metzger and others (1969), and Metzger and Smog6r (1969). Tani and others (1951) studied the effect on protective immunity against T. pallidum in rabbits immunized by carbolic acid saline suspensions of T. pallidum.…”
Section: Discussionmentioning
confidence: 99%
“…A high degree of immunity was also obtained by intramuscular injection of non-viable T. pallidum, the degree of immunity depending on the number of organisms injected during the course of immunization (Metzger and Smog6r, 1969). Thus ten rabbits immunized intramuscularly by T. pallidum with a total dose of 1-2 x 1010 given over a period of 7 wks were challenged 5 wks after completing the immunization by intradermal injection at each of four sites with 300,000 T. pallidum.…”
Section: Discussionmentioning
confidence: 99%
“…Protection has been demonstrated in the rabbit model by using complicated immunization protocols with gamma-irradiated, antiformin-treated, or 4°C "aged" treponemes (34,35,41). Although these regimens are impractical and not suitable for humans, they do demonstrate that protective immunity by vaccination is attainable.…”
mentioning
confidence: 99%